Effect of a home-based physical rehabilitation program via virtual reality on the functional outcomes of frail older adults: a quasi-experimental study - Doaa Mohamed Zein El-AbdeenMohamed; Heba Noshy Abd EL-Aziz Mohamed; Soad Hassan Abd Elhameed (Scientific Reports)
Abstract Given the rapid aging of the population in Egypt, efforts to slow down or prevent frailty. Virtual reality technology constitutes a promising rehabilitation strategy, but its effect on frailty in older adults remains inconclusive. A non-equivalent control pre, post, and follow-up test design was used with a sample of 70 prefrail or frail older adults. In 3 urbans affiliated to Dakahlia governorate, tools of data collection; Mini-Cog, Structured Interview Schedule, Survey of Health, Aging and Retirement in Europe of the Frailty Indicator (FI), Short Physical Performance Battery, and Falls Efficacy Scale. For each group, a significant improvement in frailty, physical performance, and falls from each measurement period to immediately after (p < 0.001), and within the 30-days study period while those in the control group were relatively stable over time and sometime worsen. The baseline characteristics and assessment results were similar between groups. We observed significant improvements in the intervention group in terms of frailty criteria, standing balance, gait speed, chair stand, and fear of fall. No improvements were observed in the control group, we anticipate a decrease in frailty index, and increase in standing balance, reinforcing the proven benefits of the exercise in this vulnerable population.